100 Evaluation of an interactive headache service family event: the use of patient-centred outcome measures. (December 2018) - Bullock, H; Mortimer, J; Williams, H; Hall, O; Farrell, S; Prabhakar, P
Abstract : Background: Children and families attending a specialist headache clinic were invited to attend an interactive headache day. The day aimed to offer the opportunity to meet other children and families, engage in discussion about their experiences and attend sessions delivered by a Consultant Neurologist, Clinical Psychologist, Clinical Nurse Specialists and a young adult recently transitioned to adult services. Patient centred outcome measures were used to understand the aims of those attending and assess whether they were achieved. Methods: Two interactive headache service days took place one year apart. The first day was split into separate sessions for younger children and adolescents. In response to feedback, the second day consisted of one session for all families. However, the content remained similar. Attendees were asked to complete a goal based outcome form, identifying up to three goals for attending and rating their progress towards each before the event started from 0–10 (10=goal reached). Progress was rated again at the end of the event. In 2017 9 parents and 9 children/young people returned the forms. In 2018 they were returned by 6 parents and 5 children/young people. The goals were categorised according to themes with average ratings pre and post event and change in ratings calculated. Results: There was an average increase in goal rating of 4.32 across 31 goals for parents and 3.45 across 31 goals for children/young people. Seven themes were identified; meeting others/shared experiences, education/general functioning, coping strategies, information on treatment/research/next steps, understanding of the condition, ways to support the child (parents only) and reduced migraines. Conclusions: Parents and children/young people attending an interactive headache day reported progress towards their goals. The goals largely corresponded with the aims of the team. Events such as this can form a beneficial part of the service offered to children and young people with headache conditions.